Scientific contribution of professors I.N. Osipov and A.F. Smyshlyayeva into the development of domestic pediatrics (to the 60th anniversary of pediatric faculty of Siberian State Medical University) - I. I. Balasheva (Бюллетень сибирской медицины)
The creative biography and the basic trends of labor and scientific activity of the famous scientists-pediatricians of Tomsk Medical Institute (now Siberian State Medical University) – professors I.N. Osipov and A.F. Smyshlyayeva – has been presented. Especially it has been discussed the science-philosophic papers of professor I.N. Osipov devoted to the problems of diagnosis theory, and priority researches of professor A.F. Smyshlyayeva devoted to gallbladder and biliary tracts diseases at children. Their undoubted contribution into the development of domestic pediatrics has been underlined.